Evaluation of bioactive substances in different parts of the root in beetroot (Beta vulgaris ssp. esculenta var. rubra) - Besbas, Mohamed El-Amine; Takácsné, Mária Hájos (Acta Agraria Debreceniensis, 2024)
Beetroot, also known as Beta vulgaris ssp. esculenta var. rubra, is a root vegetable that contains a substantial quantity of bioactive elements, notably antioxidants and anti-inflammatory properties. These bioactive compounds, including betalains, phenolics, and flavonoids, contribute to the health-promoting properties of beetroot. The antioxidant and anti-inflammatory effects of beetroot have been extensively studied in preclinical and clinical settings. The active compounds in beetroot have been reported to provide benefits in reducing the risk of various diseases, our research provides a comprehensive analysis of the bioactive compounds the inner and outer skin parts of the root structure. The findings aim to contribute to a deeper understanding of the potential health benefits associated with specific beetroot root components. Furthermore, the results have implications for optimising beetroot cultivation and processing for enhanced nutritional value. This research not only advances our knowledge of the phytochemical profile of beetroot outer skin but also offers valuable insights into the broader field of plant biochemistry and its applications in promoting human health and nutrition.